2018
DOI: 10.1124/mol.117.110510
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Plasma Membrane Levels Increased by the Progesterone Receptor Membrane Component 1

Abstract: The insulin receptor (IR) is a ligand-activated receptor tyrosine kinase that has a key role in metabolism, cellular survival, and proliferation. Progesterone receptor membrane component 1 (PGRMC1) promotes cellular signaling via receptor trafficking and is essential for some elements of tumor growth and metastasis. In the present study, we demonstrate that PGRMC1 coprecipitates with IR. Furthermore, we show that PGRMC1 increases plasma membrane IR levels in multiple cell lines and decreases insulin binding at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
(70 reference statements)
1
33
0
2
Order By: Relevance
“…Loss of PGRMC1 affects the SREBP-1/fatty acid homeostasis system , and PGRMC1 influences cell surface localization of insulin receptor and glucose transporters (Hampton et al, 2018). Chemical proteomics showed that PGRMC2 but not PGRMC1 promotes adipogenesis in 3T3-L1 preadipocytes following a gain of function interaction with a novel small molecule which displaced heme (Parker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of PGRMC1 affects the SREBP-1/fatty acid homeostasis system , and PGRMC1 influences cell surface localization of insulin receptor and glucose transporters (Hampton et al, 2018). Chemical proteomics showed that PGRMC2 but not PGRMC1 promotes adipogenesis in 3T3-L1 preadipocytes following a gain of function interaction with a novel small molecule which displaced heme (Parker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that PI3K/Akt signaling in DM cells required PGRMC1 Y180, which was the sole difference to TM cells. PGRMC1 has long been recognized as a modulator of Akt activity, with cell type-specific effects (Hampton et al, 2018;Hand and Craven, 2003;He et al, 2018;Liu et al, 2009;Neubauer et al, 2008;Zhu et al, 2013;Zhu et al, 2017). This predicted activation of signals by removal of the putative inhibitory CK2 consensus sites in the DM protein Neubauer et al, 2008) was dependent upon Y180 because TM (which differs from DM by a single oxygen atom) exhibited a protein expression profile that was more similar to WT than DM ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PGRMC1-associated membrane trafficking determines the cell surface localization of a number of different proteins including e.g., epidermal growth factor receptor (Ahmed et al, 2010a), insulin receptor and glucose transporters GLUT-1 and GLUT-4 in A549 lung cancer cells (Hampton et al, 2018), glucagon-like peptide-1 (GLP-1) receptor complex in pancreatic beta cells , synaptic vesicles in the central nervous system (Izzo et al, 2014), and membrane progestin receptor α (mPRα) in rat granulosa cells (Thomas et al, 2014) and maturing zebrafish oocytes (Aizen et al, 2018). The translocation of transmembrane proteins such as membrane receptors to the cell surface could underlie much of the biology attributed to PGRMC1 (Ahmed et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Sabbir [25] recently reported that PGRMC1 induced a P4-dependent metabolic change resembling the Warburg effect in HEK293 cells, which was associated with changes in PGRMC1 stability, post-translational modifications, and subcellular locations. PGRMC1 regulation of glucose metabolism is supported by its implicated mediation of the placental P4-dependent shift from aerobic towards anaerobic glucose metabolism in gestational diabetes [26], association with the insulin receptor and glucose transporters [27], and probable involvement (based upon AG-205 sensitivity) in P4-mediated increase in neuronal glycolysis [28].…”
Section: Introductionmentioning
confidence: 99%